2018
DOI: 10.3389/fped.2018.00007
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Calcium Dictates Onset, Severity, and Recovery of Diarrhea in a Child with Immune-Mediated Enteropathy

Abstract: Diarrhea causes monovalent and divalent ion losses that can influence clinical outcome. Unlike the losses of monovalent ions, such as Na+, K+, Cl−, and HCO3−, which are generally large in quantity (osmoles) and therefore determine the severity of diarrhea, the losses of divalent ions are relatively small in osmoles and are often overlooked during diarrheal treatment. Studies now suggest that despite divalent ions being small in osmoles, their effects are large due to the presence of divalent ion-sensing recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…We also predict that, when this CaSR-mediated anti-secretory protection is decreased or lost, such as in children with a negative calcium balance or nutrient deprivation, this and other diarrheal diseases would be anticipated to be more common. Additionally, the diarrheal symptoms would be more severe, and the disease duration would be longer, as shown 62 64 . This CaSR protection theory may also explain why increasing calcium intake is effective in reducing the severity and duration of diarrhea resulting from enterotoxigenic Escherichia coli 65 and other enterotoxin-producing infections 66 .…”
Section: Discussionmentioning
confidence: 97%
“…We also predict that, when this CaSR-mediated anti-secretory protection is decreased or lost, such as in children with a negative calcium balance or nutrient deprivation, this and other diarrheal diseases would be anticipated to be more common. Additionally, the diarrheal symptoms would be more severe, and the disease duration would be longer, as shown 62 64 . This CaSR protection theory may also explain why increasing calcium intake is effective in reducing the severity and duration of diarrhea resulting from enterotoxigenic Escherichia coli 65 and other enterotoxin-producing infections 66 .…”
Section: Discussionmentioning
confidence: 97%
“…CaSR can activate various tissue-specific signalling pathways upon agonist or allosteric activator stimulation and thus play critical roles in various biological processes, such as hormone secretion, cell proliferation, cell differentiation, apoptosis, ion channel activity, cell membrane potential regulation and modulation of signalling molecules for gene and protein expression (5,6,10,11) . Abnormal CaSR expression and/or activity are closely related not only to disorders of the parathyroid gland but also to other diseases, such as diarrhoea, colitis and neoplasia (12)(13)(14)(15) . Therefore, CaSR is important in the maintenance of animal health.…”
mentioning
confidence: 99%
“…In addition, it has been reported that caffeine can increase the intracellular calcium levels through directly effects on metabolic phosphorylase-like enzymes (PHOS) regulation and calcium mobilization from the sarcoplasmic reticulum [41]. Our results revealed the caffeine in feces was downregulated in S50 compared with NC group and suggested it may be bene cial to a decrease in cytosolic calcium to inhibit pathophysiologic processes which resulting in diarrhea [42]. Moreover, previous studies have suggested that nuclear translocation of nuclear factor κ-light-chain-enhancer of activated B cells (NF-κB) can induce melatonin synthesis in macrophages [43].…”
Section: Feces Metabolomicsmentioning
confidence: 58%